2019
DOI: 10.1002/tox.22809
|View full text |Cite
|
Sign up to set email alerts
|

Geraniin inhibits oral cancer cell migration by suppressing matrix metalloproteinase‐2 activation through the FAK/Src and ERK pathways

Abstract: Geraniin has been reported to have numerous biological activities, including antiviral, antihypertensive, antihyperglycaemic, liver protective, antidiabetic, and apoptotic activities. However, the anti‐migration effects of geraniin on oral cancer remain elusive. In this study, we revealed the potential antitumor mechanisms of geraniin through the inhibition of the migration and invasion of human oral cancer cell lines SCC‐9 and SCC‐14. The results of gelatin zymography and Western blot assays revealed that ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 58 publications
(98 reference statements)
1
21
0
Order By: Relevance
“…Since the Mitogen-activated protein kinases (MAPK) are involved in regulating MMP-2, which is known as a metastasis pathway [ 23 , 24 ], the effects of morusin on the expressions of MAPK pathway were investigated by Western blotting assay. The results demonstrate that morusin significantly inhibited the phosphorylation of FAK, Src, and ERK1/2 in the NPC-39 cell lines, while no effect on the phosphorylation of AKT, p38, and JNK1/2 was measured ( Figure 5 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Since the Mitogen-activated protein kinases (MAPK) are involved in regulating MMP-2, which is known as a metastasis pathway [ 23 , 24 ], the effects of morusin on the expressions of MAPK pathway were investigated by Western blotting assay. The results demonstrate that morusin significantly inhibited the phosphorylation of FAK, Src, and ERK1/2 in the NPC-39 cell lines, while no effect on the phosphorylation of AKT, p38, and JNK1/2 was measured ( Figure 5 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…When natural products affect cancer cells at high concentrations, this can be explained by their potency to induce apoptosis 21 . However, low cytotoxic concentrations of compounds are commonly chosen for migration studies 38–40 . As for POMx, at low cytotoxic concentrations it also shows wound healing inhibition in breast cancer stem cells 16 .…”
Section: Discussionmentioning
confidence: 99%
“…OSCC metastasis can be regulated though many signaling pathways, such as MAPK, PI3 K/AKT, and FAK/Src [35][36][37]46,47]. Our results showed that the cell migration ability was increased in CA III overexpression cell lines and decreased after FAK inhibitor treatment (Figure 4 C).…”
Section: Discussionmentioning
confidence: 64%
“…Numerous studies have speculated that the FAK/Src pathway participates in oral cancer migration [34][35][36][37]. Therefore, we also determined whether CA III could regulate the EMT and migration ability though Src and FAK signaling pathways.…”
Section: Ca III Promotes the Migration Ability Through The Fak/src Pamentioning
confidence: 92%